P1435RELATIONSHIP BETWEEN INTRA-DIALYTIC OXYGEN EXTRACTION RATIO (OER) CHANGE AND IDH. (6th June 2020) - Rotondi, Silverio; Tartaglione, Lida; Muci, Maria Luisa; Caissuti, Sara; Pasquali, Marzia; Mazzaferro, Sandro
Abstract: Background and Aims: Intradialytic hypotension (IDH) involves a reduced tolerance to hemodialysis (HD), a poor quality of life and is associated with mortality. Intradialytic monitoring systems (blood pressure, heart rate, volemia) are not able to identify patients at greater risk of IDH. IDH is a hemodynamic phenomenon and attention has recently been given to the evaluation of oxygen saturation to evaluate its role in IDH. Oxygen Extraction Ratio (OER), the ratio between SaO2 and ScvO2, is a parameter used to monitor parenchyma oxygen consumption and stress. Recent evidence showed that HD patients with a greater delta OER (ΔOER) during HD (threshold 40%)had higher mortality risk. OER could be a new monitoring instrument to measure hemodialysis induced sub-clinical parenchyma hypoxia and stress, two elements included in the pathogenesis of IDH. The aim of the study was to evaluate the relationship between OER and IDH incidence. Method: Inclusion criteria: age ≥18 years, chronic HD treatment by means of permanent jugular CVC, no evidence of acute underlying illness. We evaluated OER ([(SaO2 − ScvO2)/SaO2] × 100) before HD and at 15', 30', 60' and post HD in three HD sessions ( HD OER sessions ). For the statistic analysis we considered for each patient the median OER value obtained from the three HD OER sessions. Then we started the follow-up study with a minimum follow-up of three months and end follow-up of two years, to record IDH (defined according to K/DOQI guidelines) for each patient. We divided the population in two groups using as a threshold the median percentage number of IDH in our population and evaluate the differences between the obtained two groups in pre HD OER, Delta OER and intradialytic OER trends. Results: During the follow-up period (mean 12 ± 1.2 months), we enrolled 28 patients with permanent jugular CVC: 13 males and 15 females, aged 74±2.6 years, HD vintage 46 ± 6.5 months. The HD OER sessions for each patient were asymptomatic. Pre HD OER was 34 ± 1.4, post HD OER 46 ± 1.8, with a Delta OER of 39 ± 5 %. OER change during HD was evident since after 15 minutes (OER% 15': 40 ± 1.2 p<.001) and continued to increase progressively (OER% end HD 46 ± 1.8; p<.0001). During the follow up period we monitored 4342 HD sessions of which 186 with IDH, the median incidence of IDH was 3.6% of all HD sessions. We divided patients into two groups based on the median value of IDH incidence: ( IDH % ≤ 3.6 and IDH % > 3.6) . The two groups were not different for age (76 ± 2.4 vs 73 ± 3.0 years; p <ns), HD vintage (52 ± 8.6 vs 40 ± 4.0 months; p <ns), systolic (125 ± 3.2 vs 129 ± 4.0 mmHg; p <ns) and diastolic blood pressure (67 ± 2.2 vs 70 ± 2.2 mmHg; p <ns) and heart rate (70 ± 2.2 vs. 76 ± 2.3 bpm; p <ns) (Tab. 2). The IDH % >3.6 group had 159 IDH out of a total of 1911 sessions (9%), while IDH % ≤ 3.6 group had 27 IDH out of 2431 sessions (0.9%). Pre HD OER values were not different between the groups while the IDH % >3.6 group had greater delta OER% than the IDH % ≤ 3.6 group (43 ± 4.8 vs. 35 ± 3.0 %; p <.05) (Figure). Evaluating the OER trend during HD session a higher ΔOER% was found at 15 minutes of HD treatment in the IDH % > 3.6 group (ΔOER 20± 3.0 % vs. 8.0 ± 3.0 %; IDH % > 3.6 group vs. IDH % ≤ 3.6 group, p <.05), data confirmed at 30' (24 ± 3.0 % vs. 13 ± 5.0 %; p <.05), and post HD (43 ± 5.0 % vs 35 ± 3.0 %; p <.05), but not at 60 minutes of HD treatment (19 ± 4.0 % vs. 17 ± 4.6 %; p <ns). Conclusion: Our data show that intradialytic ΔOER, representative of the extent of tissue hypoxic stress, identifies patients at greater risk of IDH. In particular, a ΔOER of 20% after the first 15 minutes of HD and of 43% at the end of the HD session characterizes the more hemodynamically fragile patients. The measurement of the OER can be a new and easy monitoring instrument to identify the most hemodynamically fragile patients already after the first 15 minutes of HD treatment.